Interaction between Trichoderma sp., Pseudomonas putida, and two organic amendments on the yield and quality of strawberries (Fragaria x annanasa cv. San Andreas) in the Huaral region, Peru - Huasasquiche, Lucero; Ccori, Thania; Alejandro, Leonela; Cántaro Segura, Héctor; Samaniego, Tomás; Solórzano, Richard (MDPI, 2024)
Strawberry cultivation holds significant economic and social promise within Peruvian fruit production. However, conventional management practices have led to the excessive use of agrochemicals in this crop. This study proposes an organic approach to strawberry production, integrating less environmentally harmful technologies. The aim was to assess microbial inoculation by using Trichoderma sp. and Pseudomonas putida and the application of organic amendments on strawberry seedlings of the commercial cultivar “San Andreas”. A field experiment was established with evaluations in the vegetative and productive stages. Results indicate that the co-inoculation of Trichoderma sp. and Pseudomonas putida increased leaf area by 7%, and enhanced the aerial part’s fresh and dry biomass by 13% and 28%, respectively, compared to treatment without microbial inoculation. Concurrently, compost application increased the leaf number and aerial dry biomass by 22% and 19% at the end of the vegetative stage, respectively, compared to treatment without organic amendment. In addition, it reduced the days for flowering, maintaining the fruit’s physicochemical attributes. Regarding yield, the amendments application significantly enhanced fruit weight per plant by 40%, especially when applied together with Trichoderma sp., and co-inoculation increased the number of fruits per meter square by 22%. These findings highlight the potential of technologies such as microbial inoculation and organic amendments to enhance strawberry yields and to gradually reduce the use of synthetic fertilizers.